Design of a Smart Street Light-Integrated Electromec-hanical System for Willow Catkin Control - Zhou Ting; Yuan Ye; Yin Xue; Liu Yuqian; Sun Junxiu; Qi Fenghua (E3S Web of Conferences)
Aiming at the lack of development of extended functions for environmental management and failure to fully utilize the potential of streetlights as urban infrastructure, this study proposes a modular intelligent streetlight system integrating electrostatic adsorption and resource recycling. By integrating electrostatic spinning technology (electric field strength of 15 kV/m), photovoltaic power generation (conversion efficiency ≥21%) and bionic water-collecting device (water-collecting efficiency of 85%), an urban infrastructure with environmental purification function is constructed. The experimental data confirmed that under the working conditions of 30%-90% relative humidity and 0-15 m/s wind speed, the system’s willow capture efficiency reaches (85±3)% (n=5), of which (80±2.1)% is still maintained at 90% humidity (p<0.01, ANOVA), and the comprehensive energy efficiency is improved by 42.7% compared with that of the traditional street light (CI: 39.5%-45.8%). After 0.5 MPa pulse spray treatment, the willow residue was significantly reduced to (5.2±0.7)% (Δ=75.3%)”. This study provides a scalable electrostatic adsorption technological solution for urban willow wadding pollution treatment.